Strategi Pemasaran Jasa Balik Nama Sertifikat Tanah di Kantor Notaris Etik Pudji Lestari, S.H., M.Kn - Novita Setyoningrum; Wulan Destari Natalia (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2021)
The marketing mix is one of the aspects considered by the buyer to be able to decide on the purchase of a product, both goods and services. Services are also referred to as the provision of performance or invisible activities from one party to another. The Notary Office / PPAT Etik Pudji Lestari, SH., MKn has implemented 7P with activities in the form of product, price, place, promotion, people, process and physical awareness in its marketing mix so as to help encourage client interest to take care of returning the name of the certificate to the Notary / PPAT Ethics Pudji Lestari, SH., MKn. In planning the marketing mix, it is necessary to have sequential stages with an emphasis on the circumstances owned by the company. The success or failure of a marketing program carried out by a company depends on how the company is able to build a marketing program that has good effectiveness and efficiency for the implementation of product marketing.